Anatomical variation in vascular attributes of wood of Astronium fraxinifolium Schott trees from the soil loan area of a hydroelectric plant and an experimental plantation - Goncalves, Ricardo De Almeida [UNESP]; Tomazello Filho, Mario; Teixeira De Moraes, Mario Luiz [UNESP]; Cambuim, Jose [UNESP]; Martins, Aline Redondo [UNESP] (Elsevier B.V., 2020)
The survival of plants is linked to their capacity to respond to environmental selection. Plants may show different wood anatomical features related to survival, such as an increase in parenchyma and decrease in diameter of vessels. The aim of this study was to investigate the wood anatomical features of male and female Astronium fraxinifolium trees growing in environments characterized by degraded and non-degraded soil. It was expected that the trees to present (i) a response to environment that would allow better hydraulic conductivity, and (ii) a wood anatomy difference according to the species' gender. The results showed that the wood anatomy differed significantly between male and female plants only in the non-degraded area. The male trees had larger rays and fibre lumens, but the fibre wall thickness and length did not differ significantly. Neither nor did the diameter and density of vessels. Comparing the areas, the wood of the impacted area showed vessels of larger diameter and lower density, larger rays and fibres with smaller lumens and thicker walls, but no significant difference in the fibre length. Some wood anatomical features in the impacted area, such as greater vessels, supported by larger rays and thicker fibre walls, were probably influenced by stress at the site. The anatomical features of female trees presented lower values than the male ones in the non-impacted area.
Keywords: Cerrado plant; Phenotypic plasticity; Wood anatomy; Xylem